Modulation of optoelectronic properties of WO3 thin film via Cr doping through RF co-sputtering - Chelvanathan, Puvaneswaran; Haque, Md. Mahfuzul; Mahjabin, Samiya; Islam, Md. Ariful; Selvanathan, Vidhya; Putthisigamany, Yoganash; Abdullah, Huda; Arith, Faiz; Md. Akhtaruzzaman; Ibrahim, Mohd Adib (Elsevier B.V., 2025)
Tungsten trioxide (WO3) has drawn significant interest for its diverse applications, including electrochromic devices, perovskite solar cells, and gas sensors among others, due to its tunable properties. This study investigates the impact of chromium (Cr) doping on WO3 thin films deposited via RF co-sputtering. X-ray diffraction and Raman spectroscopy confirmed Cr incorporation, enhancing crystallinity. UV–Vis spectroscopy verified the improvement in transmittance and revealed an increase in the energy bandgap with Cr doping. Field emission scanning electron microscopy revealed reduced grain size and increased surface roughness with higher Cr doping. Additionally, electrical measurements indicated decreased conductivity. The enhanced transmittance and widened energy bandgap suggest that Cr-doped WO3 could serve as an efficient electron transport layer in ni-p structured perovskite solar cells. These findings demonstrate that controlled Cr doping effectively tailors WO3 properties, providing valuable insights for optimizing its performance in optoelectronic applications.